2020
DOI: 10.1101/2020.09.02.279745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrete TrkB-expressing neurons of the dorsomedial hypothalamus regulate feeding and thermogenesis

Abstract: Mutations in the TrkB neurotrophin receptor lead to profound obesity in humans, and expression of TrkB in the dorsomedial hypothalamus (DMH) is critical for maintaining energy homeostasis. However, the functional implications of TrkB-expressing neurons in the DMH (DMHTrkB) on energy expenditure are unclear. Additionally, the neurocircuitry underlying the effect of DMHTrkB neurons on energy homeostasis has not been explored. In this study, we show that activation of DMHTrkB neurons leads to a robust increase in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Energy consumption mediated by thermogenesis and physical activity was furthermore induced by the activation of neurons that express TrkB in the DMH. This recent study revealed distinct neuronal populations expressing TrkB which create neurocircuitry by projections to several brain regions (raphe pallidus, PVH and preoptic area) to accurately manage energy expenditure and food intake [36]. www.videleaf.com Genetic disorders causing BDNF haploinsufficiency or TrkB inactivation provide direct evidence for the understanding of the role of BDNF in the regulation of energy balance in humans.…”
Section: The Role Of Bdnf In the Central Control Of Energy Balancementioning
confidence: 99%
“…Energy consumption mediated by thermogenesis and physical activity was furthermore induced by the activation of neurons that express TrkB in the DMH. This recent study revealed distinct neuronal populations expressing TrkB which create neurocircuitry by projections to several brain regions (raphe pallidus, PVH and preoptic area) to accurately manage energy expenditure and food intake [36]. www.videleaf.com Genetic disorders causing BDNF haploinsufficiency or TrkB inactivation provide direct evidence for the understanding of the role of BDNF in the regulation of energy balance in humans.…”
Section: The Role Of Bdnf In the Central Control Of Energy Balancementioning
confidence: 99%